2018
DOI: 10.3390/su11010121
|View full text |Cite
|
Sign up to set email alerts
|

Management of Waste Collection from Yachts and Tall Ships from the Perspective of Sustainable Water Tourism

Abstract: This article deals with the issue of waste collection from yachts and tall ships that is important from the perspective of sustainable tourism. There are, of course, procedures that regulate the passing of waste by vessels, which also apply to tourist vessels. However, the authors made an attempt to analyze the process of waste collection carried out under non-standard conditions, i.e., during a mass event held at the port of the Tall Ships Races final, which took place in 2017 in Szczecin. Many yachts and tal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 19 publications
(13 citation statements)
references
References 19 publications
0
8
0
Order By: Relevance
“…There is extant research related to sailing tourism that focuses on its sustainability aspects (Łapko et al, 2019;Trstenjak et al, 2020); challenges faced in its development (Silveira et al, 2018); safety and security (Kasum et al, 2018); smart communication (Benevolo & Spinelli, 2018); and contribution to local economies (Ivanić et al, 2018). There have also been studies that evaluated the constraints on nautical tourism (Jovanovic et al, 2013) and dimensions of yachting tourism experiences (Mikulić et al, 2015;Pipere et al, 2020).…”
Section: Sailing Tourismmentioning
confidence: 99%
See 1 more Smart Citation
“…There is extant research related to sailing tourism that focuses on its sustainability aspects (Łapko et al, 2019;Trstenjak et al, 2020); challenges faced in its development (Silveira et al, 2018); safety and security (Kasum et al, 2018); smart communication (Benevolo & Spinelli, 2018); and contribution to local economies (Ivanić et al, 2018). There have also been studies that evaluated the constraints on nautical tourism (Jovanovic et al, 2013) and dimensions of yachting tourism experiences (Mikulić et al, 2015;Pipere et al, 2020).…”
Section: Sailing Tourismmentioning
confidence: 99%
“…The European Parliament suggested that more projects or programmes should be focused on sailing tourism, which requires different solutions and management models compared to mass tourism (European Parliament, 2019). An increasing number of studies have investigated the topic of sailing tourism, but most of them shed light on sustainability, safety, security, and smart communication aspects, and tourist satisfaction with sailing tourism has been afforded insufficient attention (González et al, 2018;Łapko et al, 2019;Silveira et al, 2018;Trstenjak et al, 2020). Without an adequate assessment of the impact of marina attributes on tourist satisfaction, sailing destinations may not be able to map out successful marketing and development strategies and effectively increase destination attractiveness.…”
Section: Introductionmentioning
confidence: 99%
“…Studies show that water governance can positively or negatively affect tourism. e improved water governance benefits tourism growth and provides another development path for the tourism industry [10]. A good image of water governance increases the competitiveness and attractiveness of a tourism destination; good water governance illustrates that the destination has attractive scenery and resources for aquatic tourism activities [11].…”
Section: E Impact Of Water Governance On Tourismmentioning
confidence: 99%
“…Thus, McLaughlin et al [13] noted that the current treatment systems (Oil Water Separators) for on-board bilge water treatment (Annex I) generally reduced the majority of other potentially harmful pollutants, which are not currently regulated, with the exception of some heavy metals. A different approach to port waste handling was tackled by Lapko et al [14]. In this case, the authors analyzed the waste collection from yachts and tall ships in a multi-day mass event: A tall ships race with two million tourists taking part.…”
Section: A Brief Literature Reviewmentioning
confidence: 99%